SEWAGE WATER TREATMENT AND ITS EFFECT ON THE CLEANLINESS OF WATER: A REVIEW FROM ISLAMIC AND SCIENCE PERSPECTIVE - Mohd Salleh, Mohd Mahyeddin; Mohd Safian, Yasmin Hanani; Azhari, Syaza; Ahmad Thaidi, Hussein Azemi (Jurnal Fiqh, 2024)
Due to the water combining with feces, sewage water found in the Sewage Treatment Plant (STP) is classified as mutanajjis. However, the wastewater cleaned with current technology in STP has created concerns, particularly among Muslims, over whether it can be classified as muṭlaq water or not. The purpose of this study is to compare the cleaning mechanism from an Islamic perspective with the sewage water treatment technique in Indah Water Konsortium (IWK) Malaysia. Next, to examine the treated sewage water and its impact on the law of ṭahārah in Islam. This study uses a qualitative approach using data collection techniques by document analysis, observations at the Regional Sewage Water Treatment Plant (RSTP) KL-Titiwangsa 2 owned by Indah Water Konsortium (IWK) Malaysia, interviews with Shariah and water experts, and laboratory analysis. The results of the study revealed that the wastewater treatment technology at RSTP Serantau KL-Titiwangsa 2 can change the status of water from mutanajjis to muṭlaq because it meets all the criteria for muṭlaq water set by the fuqaha. Through the results of laboratory analysis, the treated sewage water is categorized in the same category as muṭlaq water. Therefore, the water can be used for ṭahārah purposes. It also sheds light on the aspects of environmental sustainability from an Islamic perspective.